O ensino da Matemática para além do racionalismo - ARAÚJO, Maxwell Gonçalves (2009)
From Plato to the present were the many philosophies that tried to acquire the mathematical knowledge of a unique design. Still, the rationalist perspective of seventeenth and eighteenth centuries, almost to absolute, always has a great influence, even today, in Mathematics Teaching. In this sense, despite the implementation of actions aimed at alleviating the rational view, the problems relating to education and the difficulties in learning Mathematics, persist. This believe/do/think/teach a school mathematics, without any questioning, that is, without a critical and reflective thinking has been criticized, particularly by means of Critical Mathematics Education, which takes one of his biggest Skovsmose referents. In view of this, it is necessary to reflect on this relationship is conceived between mathematical knowledge and society. In this work we demonstrate the importance of historical/philosophical/social teaching of mathematics, so that the processes of teaching and learning have a true social significance. Accordingly, no dogma, the individual must be craftsman of his own education that will guarantee a more harmonious and integral development of more humane. For this, we need to think/rethink the teaching of mathematics, leading to a significant learning really can not be alien to the construction of mathematical knowledge. To do this, this education should be focused beyond rationalism.